Accessible musical instruments: an extension project of the Federal University of Pernambuco (Orfeu, 2023)
Projects and research in the area of ​​music technology, accessible luthiery and instrumental adaptations need to be further encouraged if we really want a more inclusive society and if we want to offer the same study rights and musical performance field for people with and without disabilities. Therefore, this article presents 3 electronically created/adapted musical instruments for people with motor or cognitive difficulties. Such instruments were developed within an extension project of the Music Department of the Federal University of Pernambuco, in 2018. The project aimed to develop accessible and alternative musical instruments for audiences that contemplate diversity. The main theoretical basis was Assistive Technology, which aims to promote adaptations for people with disabilities and the methodology of the article is an experience report. The result presented here describes and indicates possible applicability for the instruments created: “keyboard for feet, electronic bongo drum and electromagnetic metallophone”.
Keywords: assistive technology; accessible instruments; musical inclusion; instrumental adaptations